2020
DOI: 10.1055/s-0040-1718901
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus for Kaposiform Hemangioendothelioma and Kasabach-Merritt Phenomenon in a Neonate

Abstract: We present a case of a neonate born with kaposiform hemangioendothelioma (KHE), complicated by Kasabach-Merritt phenomenon (KMP) and other serious conditions, who was successfully treated with sirolimus. In addition to complications from thrombocytopenia and fluid overload, during the course of therapy, our patient experienced supratherapeutic drug levels at the commonly accepted starting dose of sirolimus. Patients with KHE and KMP should be closely monitored for potential complications of both the initial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Once infection symptoms occur during sirolimus treatment, it is necessary to actively treat them to avoid severe consequences. To reduce the side effects of sirolimus, some researchers have attempted to reduce its dosage [ 10 , 18 , 19 ]; the therapeutic dose was reduced to half the standard dose and even lower, and very good results were obtained. Among the cases in the present study, the standard dose (0.8 mg/L, bid) was used for all infants.…”
Section: Discussionmentioning
confidence: 99%
“…Once infection symptoms occur during sirolimus treatment, it is necessary to actively treat them to avoid severe consequences. To reduce the side effects of sirolimus, some researchers have attempted to reduce its dosage [ 10 , 18 , 19 ]; the therapeutic dose was reduced to half the standard dose and even lower, and very good results were obtained. Among the cases in the present study, the standard dose (0.8 mg/L, bid) was used for all infants.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple treatment regimens have been used for KHE with KMP with varying success, and the most recent randomized clinical trials reported encouraging results of using combination therapy with sirolimus plus prednisolone ( 5 , 12 , 15 ). Sirolimus, an inhibitor of the mammalian target of rapamycin (mTor), has been demonstrated to show satisfactory efficacy as oral administration in the treatment of KHE ( 16 19 ). There are a number of published reports on the use of sirolimus monotherapy in KHE with KMP, and it appears to be effective and safe in patients with life-threatening vascular anomalies ( 18 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…To find a more suitable dose for neonates, we review the literature related to sirolimus used in neonates with other disorders. One case report suggested a dose of 0.4 mg/m 2 twice a day based on the goal levels clinically[ 11 ]. One study showed the proposed dose regimens for each age group, such as 0.4 mg/m 2 /dose twice a day for 0-1 mo, 0.5 for 1-2 mo, 0.6 for 2-3 mo, and so on, which was based on the developmental changes in pharmacokinetics[ 12 ].…”
Section: Discussionmentioning
confidence: 99%